Non-Plasmon Resonances in the E-polarized Plane Wave Scattering and Absorption by a Circular Dielectric Wire with Partial Graphene Cover - Mikhailikova, Iryna; Dukhopelnykov, Sergii V.; Sauleau, Ronan (Conference proceedings (IEEE International Scientific Conference Electronics and Nanotechnology. Online), 2022)
We analyze how the total scattering cross-section (TSCS) and absorption cross-section (ACS) of a circular dielectric rod, illuminated with the E-polarized plane wave, is modified by a conformal graphene strip of arbitrary angular width and chemical potential. In the core of our treatment, there is a dual series equation where the unknown are the field angular Fourier harmonics. We subject this equation to the Inverse Discrete Fourier Transform (IDFT) that yields a Fredholm second kind matrix equation. Such a procedure guarantees the convergence of the obtained numerical results. We present the normalized TSCS and ACS versus the angular width of graphene strip and the frequency in the range from the statics to 1 THz. These plots convincingly demonstrate that the resonances on the lowest non-plasmon natural modes of the considered scatterer are still tunable due to the tunability of graphene's conductivity.